Proceedings of the 2014 Australasian Document Computing Symposium 2014
DOI: 10.1145/2682862.2682864
|View full text |Cite
|
Sign up to set email alerts
|

Improving test collection pools with machine learning

Abstract: IR experiments typically use test collections for evaluation. Such test collections are formed by judging a pool of documents retrieved by a combination of automatic and manual runs for each topic. The proportion of relevant documents found for each topic depends on the diversity across each of the runs submitted and the depth to which runs are assessed (pool depth). Manual runs are commonly believed to reduce bias in test collections when evaluating new IR systems.In this work, we explore alternative approach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…In contrast, the automatic benchmark provides the opportunity to study the marginal relevance of the ranking, by the nature of its construction. Another advantage of our approach is that it is less influenced by a particular selection of systems from which the assessment pool is built-a problem pointed out by Jayasinghe et al (2014). Anecdotally, many participants reported that automatic collections are very effective for method development and training, since train and test performance is often nearly identical.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, the automatic benchmark provides the opportunity to study the marginal relevance of the ranking, by the nature of its construction. Another advantage of our approach is that it is less influenced by a particular selection of systems from which the assessment pool is built-a problem pointed out by Jayasinghe et al (2014). Anecdotally, many participants reported that automatic collections are very effective for method development and training, since train and test performance is often nearly identical.…”
Section: Discussionmentioning
confidence: 99%
“…A system of Cormack et al (1998) aids manual assessors in determining the relevance through interactive searching and judging. Jayasinghe et al (2014) suggest a machine learning method to obtain more resilient assessment pools for manual assessment. Yilmaz et al (2008) reduce manual assessment costs by sampling assessment pools randomly from input rankings while preferring highly ranked documents.…”
Section: Automatic Support For Manual Test Collectionsmentioning
confidence: 99%